Simulasi Monte Carlo dalam Memprediksi Disribusi Kopi Starbuck - Irawan, Dedi; Sumijan; Nurcahyo , Gunadi Widi (Jurnal Informatika Ekonomi Bisnis, 2020)
Distributing and marketing Starbuck coffee is a very important part of the company PT Vision Logistik Transindo in increasing a profit. Starbuck is a company originating from the United States headquartered in Seattle, Washington, and already has the world's largest coffee shop with 20,336 stores in 61 countries, including Indonesia. In distribution management it is very necessary to determine the Starbuck coffee needed, so that customer demand can be fulfilled. This study conducted data on Starbucks coffee distribution from 2017 to 2019. The data processing in this case uses the Monte Carlo algorithm to predict the distribution of Starbuck coffee. In accelerating data processing, this study applies a Web-based program with the PHP programming language (Hypertext Processor). The result of the test is to get the predicted results of Starbuck coffee with an accuracy level of 90%. So that the results obtained can help the company PT.Vision Logistik Transindo in increasing distribution in the coming year.